Econometric Theory Unveiled : Building Blocks for Effective Economic Analysis - Kaouthar Souad KOUDA (Pensées Genre, Penser Autrement)
This study examines the effectiveness of econometric models in quantifying relationships between economic variables and improving forecast accuracy. By integrating economic theory, mathematics and statistics, the models analyzed reveal significant correlations between price, demand and income, validating the initial hypotheses. The results show that these models provide reliable estimates for economic decision-making, supported by statistical tests that confirm the robustness of the predictions. Despite certain limitations, such as collinearity and autocorrelation, the models used demonstrate a solid ability to anticipate economic trends. The study also proposes ways of refining these models by incorporating additional variables, thereby strengthening their relevance for economic analysis in an evolving context.